2020
DOI: 10.1371/journal.pone.0237348
|View full text |Cite
|
Sign up to set email alerts
|

Does type of active workstation matter? A randomized comparison of cognitive and typing performance between rest, cycling, and treadmill active workstations

Abstract: Active workstations are associated with improved health outcomes, but differences in cognitive and typing outcomes between the types of active workstations are unclear. We addressed two main questions: (1) Are there differences in cognitive and typing performance between seated and active workstations? (2) Are there differences in cognitive and typing performance between cycling and treadmill workstations, specifically? Participants included 137 healthy young adults (74 female, mean age = 20.8 years) who compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
(136 reference statements)
0
10
0
1
Order By: Relevance
“…Twenty-nine studies investigated the effects of lowintensity dynamic contractions combined with a cog-nitive load (Table 1). Studies in this category reported an effect of concurrent load used assembly (Shaikh et al, 2012), computer work (Finsen et al, 2001b;Leyman et al, 2004), and active workstations (Larson et al, 2015;Frodsham et al, 2020) as the physical task, while cognitive tasks were instructions necessary to accomplish the physical task (Finsen et al, 2001b;Shaikh et al, 2012), or an Auditory Verbal Learning Test (Larson et al, 2015;Frodsham et al, 2020). Among the studies reporting no or small effects of concurrent load, the most common physical task was computer work (Finsen et al, 2001a(Finsen et al, , 2001bLeyman et al, 2004;Bloemsaat et al, 2005).…”
Section: Low-intensity Dynamic Contractionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-nine studies investigated the effects of lowintensity dynamic contractions combined with a cog-nitive load (Table 1). Studies in this category reported an effect of concurrent load used assembly (Shaikh et al, 2012), computer work (Finsen et al, 2001b;Leyman et al, 2004), and active workstations (Larson et al, 2015;Frodsham et al, 2020) as the physical task, while cognitive tasks were instructions necessary to accomplish the physical task (Finsen et al, 2001b;Shaikh et al, 2012), or an Auditory Verbal Learning Test (Larson et al, 2015;Frodsham et al, 2020). Among the studies reporting no or small effects of concurrent load, the most common physical task was computer work (Finsen et al, 2001a(Finsen et al, , 2001bLeyman et al, 2004;Bloemsaat et al, 2005).…”
Section: Low-intensity Dynamic Contractionsmentioning
confidence: 99%
“…Studies in this category reporting a medium or large effect of concurrent load used a range of physical and cognitive tasks, for example, computer tasks (Ekberg et al, 1995;Birch et al, 2000;Alkjaer et al, 2005), active workstations (Frodsham et al, 2020;Schellewald et al, 2021), and handgrip (Guillery et al, 2013); in combination with Stroop Color Word tests (Ekberg et al, 1995;Alkjaer et al, 2005;Schellewald et al, 2021), visual memory tasks (Guillery et al, 2013) or instructions needed to perform the physical task (Birch et al, 2000;Nino et al, 2020). Studies reporting no or small effects typically used a physical task adopted from an occupational setting, such as pipetting (Srinivasan et al, 2015(Srinivasan et al, , 2016, assembly (Biondi et al, 2021), and computer work (Ekberg et al, 1995;Birch et al, 2000;Laursen, Jensen and Ratkevicius, 2001), in combination with instructions needed to perform the physical task (Srinivasan et al, 2015(Srinivasan et al, , 2016, n-back (Biondi et al, 2021), and Stroop Color Word tests (Ekberg et al, 1995;Laursen et al, 2002).…”
Section: Executive Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Absenteeism, presenteeism and cognitive ability have been identified as companies' business performances that can be influenced by PA (Andersen et al, 2015;Frodsham et al, 2020).…”
Section: Sedentary Behaviormentioning
confidence: 99%
“…Por otro lado, la falta de existencia de perjuicio académico al introducir actividad física en las lecciones es muy positiva para la intervención y concuerda con otros programas de actividad física en el aula como los de van den Berg et al (2016) y más concretamente con estudios anteriores sobre active desks (Sherry et al, 2016) y con intervenciones de bike desks (Joubert et al, 2017;Torbeyns et al, 2017). Un estudio con adultos concluyó que no hay diferencias significativas cognitivas entre realizar tareas sentado, pedaleando o trotando en un active desk (Frodsham et al, 2020). Incluso, el reciente meta-análisis de Haverkamp et al (2020) analizó más de setenta intervenciones de actividad física en adolescentes y jóvenes encontrando que tanto las intervenciones puntuales como aquellas a largo plazo parecían ser elementos prometedores para mejorar aspectos cognitivos.…”
Section: Discusión Sobre El Impacto a Nivel De Rendimiento Académicounclassified